2005
DOI: 10.1002/sia.2122
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of oxidation behavior under dry air of neat and Ta‐alloyed furan‐resin‐derived carbons heat treated at 3000 °C

Abstract: Oxidation behavior and structural changes of furan-resin-derived carbons heat treated at 3000°C were investigated at 500 and 700°C under dry air. Thermogravimetric analysis (TGA), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) were employed to detect and understand this behavior and the changes. Effect of tantalum on antioxidation property of Ta-alloyed carbon was also analyzed. The neat and Ta-alloyed carbons had insignificant weight losses even after being kept at 500°C for 12 h, while the Ta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It has been reported that a graphitizable skin is formed on the surface even on the furan-resin-derived carbon bulk above 2500 • C [8]. It has been reported that the carbons alloyed with small amounts of Ta or Ti exhibit oxidation resistance properties [9][10][11][12]. We suggest that Ta-alloying leads to a change in the state of the Fermi energy on the carbons, which may cause the antioxidation property [11].…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…It has been reported that a graphitizable skin is formed on the surface even on the furan-resin-derived carbon bulk above 2500 • C [8]. It has been reported that the carbons alloyed with small amounts of Ta or Ti exhibit oxidation resistance properties [9][10][11][12]. We suggest that Ta-alloying leads to a change in the state of the Fermi energy on the carbons, which may cause the antioxidation property [11].…”
Section: Introductionmentioning
confidence: 90%
“…It has been reported that the carbons alloyed with small amounts of Ta or Ti exhibit oxidation resistance properties [9][10][11][12]. We suggest that Ta-alloying leads to a change in the state of the Fermi energy on the carbons, which may cause the antioxidation property [11]. However, the oxidation behavior of the * Corresponding author.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations